1998
DOI: 10.1143/jjap.37.4204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Ultrathin Mask Layers of SiO2, SiOxNy and SiNxfor Selective Area Growth of Si

Abstract: Ultrathin SiO2 and SiN x layers on Si are potential mask materials for nanoscale selective-area chemical vapor deposition (CVD) in reduced dimension. This study investigates the mask-material dependence of Si nucleation processes on these ultrathin layers. Thin layers of SiO2, SiN x and SiO x N y were formed by plasma oxidation and nitrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In our experiment, SiN x mask layers were used since they were not etched by a dilute HF solution, and mask shape did not change before and after pre-cleaning process. In addition, the surface migration length on SiN x is shorter compared to that on SiO 2 for Ga, In precursors, which facilitated the formation of flat surfaces [20]. The formation of void can be also attributed to the lower growth rate of {1 1 1} facets inside void than that of (0 0 1) plane of LT InP.…”
Section: Methodsmentioning
confidence: 97%
“…In our experiment, SiN x mask layers were used since they were not etched by a dilute HF solution, and mask shape did not change before and after pre-cleaning process. In addition, the surface migration length on SiN x is shorter compared to that on SiO 2 for Ga, In precursors, which facilitated the formation of flat surfaces [20]. The formation of void can be also attributed to the lower growth rate of {1 1 1} facets inside void than that of (0 0 1) plane of LT InP.…”
Section: Methodsmentioning
confidence: 97%
“…For plasma oxidation of the SiN x layer described in §3. 3,9,10) the the substrate surface is likely to play an important role. Related to this issue, we previously compared Si deposition processes on SiO 2 and SiN x surfaces for the purpose of selective-area growth.…”
Section: Methodsmentioning
confidence: 99%
“…Related to this issue, we previously compared Si deposition processes on SiO 2 and SiN x surfaces for the purpose of selective-area growth. 9,10) We found that the initial growth processes on these two surfaces are distinctly different when Si growth is carried out in a thermal chemical vapor deposition (CVD) mode. In particular, it was observed that the shape of the Si nuclei on SiO 2 is ball-like while those on SiN x wet on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…8) In this letter, we report the successful application of such a SiO 2 /SiN x bilayer mask structure to selective-area growth of Si. Figure 1(b) shows a schematic cross section of a Si nanostructure fabricated on the SiO 2 /SiN x bilayer mask.…”
Section: Si-rich Phasementioning
confidence: 99%